Polyculture of mullets in brackishwater using compounded feed: proximate and mineral profiles in comparison with wild mullets - Dayal, J. Syama; Ambasankar, K.; Jannathulla, R.; Kumaraguruvasagam, K.P.; Kailasam, M.; Vijayan, K. K. (Indian Journal of Fisheries, 2018)
Two stage rearing (nursery and grow-out) of two mullet species, Mugil cephalus and Liza parsia was demonstrated in a farmer’s pond. In the nursery phase, wild collected grey mullet (1.65±0.2 g) and gold spot mullet (1.03±0.1 g) fry numbering 450 and 4000, respectively were stocked in pen enclosures. After 30 days of nursery rearing, they were released into the same pond and reared for 7 months using dry pelleted feed produced in the feed mill of ICAR-Central Institute of Brackishwater Aquaculture (ICAR-CIBA), Chennai. Feed was formulated using locally available ingredients to contain 33.4% crude protein and 5.7% ether extract. The fishes were fed with crumbles (0.8 mm) and pellets (2 and 3 mm) in the nursery and grow-out phases, respectively. The production of both the mullet species together at harvest was 1262 kg ha-1 (L. parsia 851 and M. cephalus, 411 kg ha-1). The nutrient composition of the two farmed sympatric mullet species when compared with their respective wild samples showed a significant variation. Higher lipid content in the farmed fishes was observed compared to their respective wild originates. The effect of size was highly significant in lipid content, its value increasing proportionately with size (p